Ewing’s sarcoma of rib - Hossain, Sk Moazzem; Kabir, Farjana; Kamal, SM; Ghosh, Debasish Kumar (Bangladesh Medical Journal Khulna, 2018)
Ewing's sarcoma is an uncommon malignant bone tumour occuring in children, adolescents and young adults. We report a case of a 13 year old male admitted to Khulna Medical College Hospital with history of pain and swelling in chest wall for two weeks. Earlier chest X-ray showed a mass lesion in the left upper part of chest wall and erosion of first rib. Subsequent X-ray revealed left sided massive pleural effusion. CT scan revealed a mass lesion in the left upper part of chest wall originated from left first rib and left sided pleural effusion. FNAC from the mass lesion revealed features suggestive of Ewing's sarcoma. Patient was treated with chemotherapy and after first cycle there was significant improvement of all the signs and symptoms. Bang Med J (Khulna) 2017; 50 : 41-43